Promoting Self-Directed Learning through Netflix as a Learnng Aid of Listening and Speaking: An Investigation toward EFL Students’ Voices - Maharani, Raulina Suci; Afifi, Nur (Universitas Pendidikan Mandalika, 2024)
The advance of mobile technology combined with aggregating customers viewing habits have increased the growth of subcription vidio on demand (SVoD) services. Although this SVoD services potentially offer some benefits in L2 learning. Little has known about the benefit of SVoD in term of L2 learning. Therefore, this study aimed to find out EFL students’ perception in UIN Maulana Malik Ibrahim Malang about the effect of watching English movies and series in Netflix as digital L2 learning aid on their listening and speaking skills. The study used mixed-method approach focusing on sequential explanatory research design. Questionnaire and interview were used in collecting the data. The respondents for questionnaires were fifteen students of English Education Department of UIN Maulana Malik Ibrahim Malang, and the informants for the interview were five students. Then they were analyzed and interpreted through percentage and qualitative procedures. The findings indicated that English Education Department students have positive perception about Netflix as digital L2 learning aid. It showed that Netflix has direct influence in comprehending English Education Department Students’ listening and speaking skills.